Past and current perspective on new therapeutic targets for Type-II diabetes - Patil PD; Mahajan UB; Patil KR; Chaudhari S; Patil CR; Agrawal YO; Ojha S; Goyal SN (Dove Medical Press, 2017)
Pradip D Patil,1,* Umesh B Mahajan,1,* Kalpesh R Patil,2,* Sandip Chaudhari,1 Chandragouda R Patil,1 Yogeeta O Agrawal,3 Shreesh Ojha,4 Sameer N Goyal11Department of Pharmacology, R. C. Patel Institute of Pharmaceutical Education and Research, 2Department of Pharmacology, H. R. Patel Institute of Pharmaceutical Education and Research, 3Department of Pharmaceutics and Quality Assurance, R. C. Patel Institute of Pharmaceutical Education and Research, Shirpur, Dhule, Maharashtra, India; 4Department of Pharmacology and Therapeutics, College of Medicine and Health Sciences, United Arab Emirates University, Abu Dhabi, UAE *These authors contributed equally to this workAbstract: Loss of pancreatic β-cell function is a hallmark of Type-II diabetes mellitus (DM). It is a chronic metabolic disorder that results from defects in both insulin secretion and insulin action. Recently, United Kingdom Prospective Diabetes Study reported that Type-II DM is a progressive disorder. Although, DM can be treated initially by monotherapy with oral agent; eventually, it may require multiple drugs. Additionally, insulin therapy is needed in many patients to achieve glycemic control. Pharmacological approaches are unsatisfactory in improving the consequences of insulin resistance. Single therapeutic approach in the treatment of Type-II DM is unsuccessful and usually a combination therapy is adopted. Increased understanding of biochemical, cellular and pathological alterations in Type-II DM has provided new insight in the management of Type-II DM. Knowledge of underlying mechanisms of Type-II DM development is essential for the exploration of novel therapeutic targets. Present review provides an insight into therapeutic targets of Type-II DM and their role in the development of insulin resistance. An overview of important signaling pathways and mechanisms in Type-II DM is provided for the better understanding of disease pathology. This review includes case studies of drugs that are withdrawn from the market. The experience gathered from previous studies and knowledge of Type-II DM pathways can guide the anti-diabetic drug development toward the discovery of clinically viable drugs that are useful in Type-II DM.Keywords: Type-II diabetes mellitus, therapeutic targets, discontinued drugs, insulin resistance